Designed Build Information System in Unikom Four-Wheeled Parking Lot based on Image Processing - Leonardo Satrio Tegar (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2016)
Increasing the number of cars and the lack of information vacant land for parking areas is often a major problem for prospective users of the car to find a parking lot that is still available. With the existence of such cases is very much needed parking space information automatically and intelligently, using image processing (image processing) which can act as a detector of parking space is still available and already filled in the building in realtime. Then later users candidate parking lots will have no trouble finding the location of their parking space will occupy. After doing the design tool and apply for testing, the system can perform the detection of land that has been provided. Besides, the system is able to calculate the number and determine its location with a 100% success rate of any condition that has been tested.